2020
DOI: 10.3390/su12062378
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Features of Costal Waterfronts: Historical Aspects and Planning Issues

Abstract: This paper investigates the relationship between different factors that impose on the productive and settlement structures on coastal areas through an analysis carried out on the Italian Adriatic Sea coast. In the panorama of medium-and small-size cities, the relationship between the city, the territory, and the sea very often plays an important role. The main issue of this article is to expose a methodology developed for the definition of landscape quality objectives in the planning of the coast of a region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Over the past two decades, there has been more interest in developing waterfronts around the world to improve the image of coastal cities, as the renewal of the waterfront is capable of linking with the past and the future in addition to providing opportunities for development. In spite of the challenges that the historical cities face in developing waterfronts, the effective planning of these cities focuses on the possibility of making use of public spaces while preserving their historical value many problems have recently resulted in the ineffective planning of the policies followed by some cities, which showed that the urban quality of the waterfronts was not suitable in most cases (Cialdea 2020).…”
Section: (Orianna Giovinazzi 2010)mentioning
confidence: 99%
“…Over the past two decades, there has been more interest in developing waterfronts around the world to improve the image of coastal cities, as the renewal of the waterfront is capable of linking with the past and the future in addition to providing opportunities for development. In spite of the challenges that the historical cities face in developing waterfronts, the effective planning of these cities focuses on the possibility of making use of public spaces while preserving their historical value many problems have recently resulted in the ineffective planning of the policies followed by some cities, which showed that the urban quality of the waterfronts was not suitable in most cases (Cialdea 2020).…”
Section: (Orianna Giovinazzi 2010)mentioning
confidence: 99%
“…If calculated since 2003, the total land lost is 46 meters with an annual average of 3.54. Cialdea [46] stated that the Urban Beach Plan also experienced an extraordinary abrasion phenomenon due to the construction of the Termoli Port. This result is also supported by the research of Mohammed et al [47], which states that human activities significantly affect the rate of soil erosion (or, in this study is abrasion).…”
Section: Coastal Changes Due To Abrasion 2003-2020mentioning
confidence: 99%
“…In this boundary space, over the years, different elements have been built [3] that reference and symbolise the sacred characteristics of the coastal landscape [4]. The landscape considered sacred reflects and preserves the fundamental ideas and values of society and serves as an important factor of continuity over time, ensuring the transmission of a wide range of historical information to future generations [5,6]. The most culturally and historically relevant sacred elements built along the coast are found in geomorphologically significant places [7], such as the mouth of a river on the sea or the edge of a promontory.…”
Section: Introductionmentioning
confidence: 99%